Pandemic communication in times of populism: Politicization and the COVID communication process in Brazil, Poland, Serbia and the United States - Hallin, Daniel C.; Mihelj, Sabina; Ferracioli, Paulo; Rao, Nithyanand; Vanevska, Katarzyna; Stojiljković, Ana; Klimkiewicz, Beata; Rothberg, Danilo [UNESP]; Štětka, Václav (Elsevier, 2024)
This paper explores patterns of communication during the COVID-19 pandemic in four countries with right-wing populist governments during that period, Brazil, Poland, Serbia and the United States, based on interviews with key actors involved in that process. We look at a number of characteristics normally associated with populist rule and political culture likely to affect pandemic communication, including polarization, cultural populism hostile to expertise, personalized rule and machismo, the performance of crisis, and illiberalism. We find that many of these characteristics can be seen in patterns of pandemic communication across the four countries, but also find significant differences in the response of populist leaders between the U.S. and Brazil, on one hand, and Poland and Serbia on the other. Differences can be linked to different varieties of populism in the four countries and specifically their commitment to libertarian or more statist approaches, which also inform disparate public health policies, as well as to different levels of entrenchment of populists in positions of power. We conclude by discussing the politicization of public health and the lessons of the COVID pandemic for emergency risk communication in the era of populism.